About some aspects of D.I. Mendeleev's world-outlook - A. A. Ivanova (Тонкие химические технологии, 2009)
In this paper, the section «World outlook» of D.I. Mendeleev's book «Cherished Thoughts» is analyzed. It is shown, what, in Mendeleev's opinion, is the connection between philosophy and science, how important the problem was for him.